Decomposition and/or hydrogenation of hydrogen peroxide over Pd/Al2O3 catalyst in aqueous medium: factors affecting the rate of H2O2 destruction in presence of hydrogen - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Applied Catalysis A-General, 2007)
Hydrogen peroxide destruction by its decomposition and/or hydrogenation to water in the presence of H-2 over Pd(5 wt.%)/Al2O3 catalyst in an aqueous reaction medium, similar to that used in the H-2-to-H2O2 oxidation, has been thoroughly investigated at different reaction conditions. The H2O2 destruction is strongly influenced by the oxidation state of Pd in the catalyst and also by the presence of different halide anions (viz. F-, Cl-, Br- and I-) in the acidic aqueous medium or in the catalyst, depending upon the concentration of halide anions. The cations associated with halide anions have, however, a little or no influence on the H2O2 destruction. The iodide anions strongly poisoned the catalyst, even at their very low concentration. The fluoride anions have only a small effect on the H2O2 destruction. The chloride or bromide anions drastically inhibit the rapid H2O2 decomposition, but promote the slower H2O2 hydrogenation. The H2O2 destruction reactions are strongly influenced by the halide anion and acid concentrations. The presence of acid (protons) plays a very important role in drastically reducing the H2O2 destruction, particularly in the presence of chloride anions. Both in the presence and absence of Cl- or Br- anions, the H2O2 destruction activity of the catalyst is markedly reduced because of the oxidation of Pd but it is drastically increased due to the presence of H-2. A plausible reaction mechanism for the rapid H2O2 decomposition and slower H2O2 hydrogenation reactions, prevailing under the different reaction conditions, has also been discussed. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: decomposition of H2O2; halide anions as catalyst promoter or indicator; Hydrogen peroxide; hydrogenation of H2O2; Pd/Al2O3

Direct formation of H2O2 from H-2 and O-2 and decomposition/hydrogenation of H2O2 in aqueous acidic reaction medium over halide-containing Pd/SiO2 catalytic system - Samanta, Chanchal; Choudhary, Vasant R. (Catalysis Communications, 2007)
Formation of H2O2 from H-2 and O-2 and decomposition/hydrogenation of H2O2 have been studied in aqueous acidic medium over Pd/SiO2 catalyst in presence of different halide ions (viz. F-, Cl- and Br-). The halide ions were introduced in the catalytic system via incorporating them in the catalyst or by adding into the reaction medium. The nature of the halide ions present in the catalytic system showed profound influence on the H2O2 formation selectivity in the H-2 to H2O2 oxidation over the catalyst. The H2O2 destruction via catalytic decomposition and by hydrogenation (in presence of hydrogen) was also found to be strongly dependent upon the nature of the halide ions present in the catalytic system. Among the different halides, Br- was found to selectivity promote the conversion of H-2 to H2O2 by significantly reducing the H2O2 decomposition and hydrogenation over the catalyst. The other halides, on the other hand, showed a negative influence on the H2O2 formation by promoting the H-2 combustion to water and/or by increasing the rate of decomposition/hydrogenation of H2O2 over the catalyst. An optimum concentration of Br- ions in the reaction medium or in the catalyst was found to be crucial for obtaining the higher H2O2, yield in the direct synthesis. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Br- catalyst promoter; direct H2O2 formation; H2O2 decomposition; Pd/SiO2 catalyst

Direct oxidation of hydrogen to hydrogen peroxide over Pd (or PdO)/Al2O3 in aqueous reaction medium: influence of different acids and halide anions in reaction medium on formation and destruction of H2O2 - Choudhary, Vasant R.; Ingole, Yugesh V.; Samanta, Chanchal; Jana, Prabhas (Industrial & Engineering Chemistry Research, 2007)
Effects of different mineral acids (viz. H2SO4, H3PO4, HNO3, HCl, HBr, and HI), acid (H3PO4) concentration, different halide anions (viz. F-, Cl-, Br-, and I-), and halide anion concentration in aqueous reaction medium on the H2O2 formation (in H-2-to-H2O2 oxidation) and/or on the H2O2 destruction (by H2O2 decomposition and hydrogenation) activities of Pd (or PdO)/Al2O3 catalyst (at 300 K and atmospheric pressure) have been thoroughly investigated. Among the different halide anions, Br- anions are most effective for promoting the H2O2 formation and inhibiting the H2O2 destruction by both the H2O2 decomposition and/or hydrogenation. The cations associated with the halide anions, however, have only a little or no influence on both the H2O2 formation and destruction. The concentration of the different halide anions has a strong influence on the H-2 conversion and H2O2 formation and destruction activities of the Pd/Al2O3. The H2O2 formation activity in the presence of Br- or Cl- anions is highest at the optimum concentration of halide (about 1.0 mmol/dm(3)). it is also highest at the optimum concentration of phosphoric acid (between 0.1 and 0.3 mol/dm(3)). In general, the H2O2 formation is increased with decreasing the H2O2 destruction activity of the catalyst, indicating a close relationship between the two. Br- anions act as an excellent catalyst promoter for Pd/Al2O3 catalyst, but they show only a small promoting effect for PdO/Al2O3 catalyst. The next choice for halide promoter for Pd/Al2O3 catalyst is Cl- anions. F- and I- anions are, however, catalyst inhibitor and strong poison, respectively, for the H2O2 formation. At the same concentration, Br- anions are more effective than Cl- anions for inhibiting the H2O2 destruction reactions over Pd/Al2O3 Catalyst. For both halide promoters (Cl- and Br-), the net H2O2 formation is controlled by the H2O2 hydrogenation rather than by the H2O2 decomposition.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007

Direct synthesis of H2O2 from H-2 and O-2 over Pd/H-beta catalyst in an aqueous acidic medium: influence of halide ions present in the catalyst or reaction medium on H2O2 formation - Samanta, Chanchal; Choudhary, Vasant R. (Catalysis Communications, 2007)
The influence of different halide ions present in the catalyst or reaction medium on the performance of Pd/H-beta catalyst in the direct H2O2 synthesis in an aqueous acidic (0.03 M H3PO4) reaction medium at 27 degrees C and atmospheric pressure has been thoroughly investigated. The results showed a strong influence of both the bulk Pd oxidation state in the catalyst and the halide ions added to the reaction medium on the performance of the catalyst in the H-2 to H2O2 oxidation, H2O2 decomposition/hydrogenation reactions. The different ammonium halides impregnated reduced Pd/H-beta catalyst calcined in inert (N-2) and oxidizing (air) gaseous atmospheres also revealed that the bulk Pd oxidation state and nature of the halide ions present in the catalyst together control the overall performance of the catalyst in the H2O2 formation reaction. The presence of halide ions in reaction medium or in the catalyst significantly changes the selectivity for H2O2 formation in the direct H2O2 synthesis. Bromide ions are found to remarkably enhance the H2O2 selectivity in the direct H2O2 synthesis irrespective of the Pd oxidation state in the catalyst. The promoting action of Br- is attributed mainly to the large decrease in the H2O2 decomposition and hydrogenation activities of the catalyst and also inhibition for the non-selective H-2-to-water oxidation over the catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: direct H2O2 synthesis; H-P supported Pd catalyst; H2O2 decomposition; H2O2 hydrogenation; promoting action of bromide ions

Direct synthesis of H2O2 from H-2 andO(2) and decomposition/hydrogenation of H2O2 in an aqueous acidic medium over halide-modified Pd/Al(2)O3 catalysts - Samanta, Chanchal; Choudhary, Vasant R. (Applied Catalysis A-General, 2007)
Direct synthesis Of H2O2 from its elements was carried out in an acidic aqueous reaction medium over halide-modified oxidized and reduced Pd/ Al2O3 catalysts under very mild conditions (at 27 degrees C and atmospheric pressure). The halide ions were introduced into the catalyst by incorporating halide ions into supported Pd/gamma-Al2O3 catalyst or via depositing halide ions on the support (gamma-Al2O3) prior to Pd deposition. The H2O2 decomposition and hydrogenation over the corresponding catalysts were also carried out under the reaction conditions similar to those employed for the H2O2 synthesis in order to elucidate the factors strongly affecting the H2O2 yield/selectivity in the direct H2O2 process. The performance of halide-modified Pd/Al2O3 catalysts in the direct H2O2 synthesis revealed that halide insertion in the catalyst system prior to or after Pd deposition on the support had comparable qualitative effect on the H2O2 formation. Both the Pd oxidation state and the nature of the halide ions had strong influences on the H-2 conversion (in direct H2O2 Synthesis process) and H2O2 decomposition and/or hydrogenation reaction. While the effect of Pd oxidation state on the H2O2 formation was significant for the catalytic system containing F- and Cl- ions, the influence of the Pd oxidation state was found less important for the catalyst system containing Br- ions; the H2O2 formation selectivity increased significantly due to the presence of Br- ions, irrespective of the Pd oxidation state. The nature of the H2O2 destruction pathway (i.e. hydrogenation and/or decomposition) in the presence of hydrogen over halide-modified Pd/Al2O3 catalysts was found to be strongly dependent upon the nature of the halide ions incorporated in the catalyst during halide-modification of the catalyst. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: direct H2O2 synthesis; H2O2 decomposition; H2O2 hydrogenation; halide-modification; Pd oxidation state

Formation from direct oxidation of H-2 and destruction by decomposition/hydrogenation of H2O2 over Pd/C catalyst in aqueous medium containing different acids and halide anions - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Applied Catalysis A-General, 2007)
Direct oxidation of H-2 by O-2 to H2O2 and decomposition/hydrogenation of H2O2 (at 27 degrees C and atmospheric pressure) over Pd/C catalyst in an aqueous acidic reaction medium have been thoroughly investigated using different mineral acids (viz. 0.1 N H2SO4, H3PO4, H3BO3, HNO3, HCl, HBr or HI) and/or halide anions (viz. F-, Cl-, Br- or I-), covering their wide concentration range (0-24 mmol/dm(3)), in the reaction medium. In the absence of any externally added halide, appreciable H2O2 formation in the H2 oxidation occurred only when the medium contained HCl. However, the rates of H2O2 decomposition and hydrogenation are greatly reduced because of the presence of any acid; the influence on the H2O2 decomposition was, however, much larger for the halo acids. In the presence of acid (0.1 N H3PO4 or H2SO4), the H-2-to-H2O2 formation reaction is greatly enhanced by the externally added halide anions up to their optimum concentrations. However, above the optimum halide anion concentration, it is inhibited more than the H-2-to-water formation (parallel) reaction, causing a decrease in both the H2O2 yield and selectivity. Whereas, the H-2 conversion and H2O2 destruction activities of the catalyst are decreased continuously with increasing the halide anion (except F-) concentration. Among the halides, chloride is the best halide promoter for Pd/C catalyst in the H-2-to-H2O2 oxidation. At the optimum Cl-concentration (5.4 mmol/dm(3)), both the H-2 conversion and H2O2 yield are passed through a maximum and the H2O2 decomposition is greatly inhibited with increasing the phosphoric acid concentration. In the absence of either the chloride anions or the acid (or both) in the reaction medium, only a little or no H2O2 is formed in the H-2 oxidation and also the rate of H2O2 destruction is very fast, particularly in the presence of H-2; the rapid destruction of H2O2 is mainly due to its decomposition rather than its hydrogenation. The best H-2-to-H2O2 oxidation results are obtained at the optimum concentrations of both the acid and halide anions. In the presence of acid and chloride (or bromide) promoter, the H2O2 hydrogenation dominates the H2O2 destruction and hence the net H2O2 formation is mainly controlled by the H2O2 hydrogenation. (c) 2006 Published by Elsevier B.V.
Keywords: H2O2 decomposition; H2O2 hydrogenation; halide anion promoters; Hydrogen peroxide; oxidation of H-2-to-H2O2; Pd/C catalyst

Generation of hydrogen peroxide via the selective reduction of oxygen by hydrazine sulfate over Br-promoted Pd/Al2O3 catalyst in an aqueous medium at ambient conditions - Choudhary, Vasant R.; Jana, Prabhas; Samanta, Chanchal (Applied Catalysis A-General, 2007)
The in situ generation of H2O2 via the selective reduction of OZ by hydrazine sulfate (in an aqueous medium) has been thoroughly investigated over the Br-promoted Pd(or PdO)/Al2O3 catalyst. The influence of the following factors have been addressed in this study: (a) Br concentration (in the reaction medium or incorporated in the catalyst); (b) reaction conditions (viz. reaction time, temperature); (c) concentrations of reducing agent and phosphoric acid in the reaction medium. Decomposition of N2H4 (from NH4-H2SO4) and its reaction with H2O2 under similar reaction conditions (in the absence of O-2) have also been studied. H2O2, which is an intermediate product of the O-2 reduction, is involved in further consecutive reactions. It can be converted to water via its decomposition and/or reaction with the unconverted NZH(4). In the presence of Br promoter, the later (reaction with unconverted N2H4) is more dominant. Both the consecutive reactions are drastically retarded in the presence of protons and Br promoter. A plausible reaction mechanism has been proposed for illustrating the role of the protons and Br promoter in the selective formation of H2O2 in the O-2 reduction process. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: brominated Pd/Al2O3 catalyst; hydrazine sulfate; Hydrogen peroxide; in situ H2O2 generation; oxygen reduction; Pd/Al2O3 catalyst

Hydrogenation of hydrogen peroxide over palladium/carbon in aqueous acidic medium containing different halide anions under static/flowing hydrogen - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Industrial & Engineering Chemistry Research, 2007)
Kinetics of the hydrogenation of hydrogen peroxide (at 278 and/or 300 K) over Pd(5 wt%)/carbon in aqueous medium with or without containing acid or different halide anions (F-, Cl-, Br-, or I-) under static H-2 (i.e. batchwise) or flowing H-2 (i.e. semi-batchwise) at atmospheric pressure have been thoroughly studied. In the absence of protons or halide anions and also in the presence of F- anions, a very rapid decomposition of H2O2 (H2O2 -> H2O + 0.5O(2)) predominates over the H2O2 hydrogenation (H2O2 + H-2 -> 2H(2)O). However, in the presence of both the protons and Cl- or Br- anions, the H2O2 conversion occurs mainly by the hydrogenation reaction. The hydrogenation is found to be a zero-order reaction with respect to the H2O2 concentration, and its activation energy and frequency factor are strongly influenced by the halide anions. The hydrogenation is found to be more and more inhibited with increasing halide (Cl- or Br-) anion concentration. The cations associated with the halide anions have, however, only a very little influence on the hydrogenation. Iodide anions act as a very strong catalyst poison for the hydrogenation. In the presence of acid, the hydrogenation is very strongly influenced by the different halides, but, in the presence of halide anions (5.4 mmol/dm(3)), it is very mildly influenced by the different mineral acids (except HI). In the absence of protons, the Cl- and Br- anions are ineffective for inhibiting the rapid H2O2 decomposition. A role played by protons and halide anions for drastically inhibiting the rapid H2O2 decomposition is discussed.

Direct oxidation of H-2 to H2O2 over Pd/CeO2 catalyst under ambient conditions: influence of halide ions - Samanta, Chanchal; Choudhary, Vasant R. (Chemical Engineering Journal, 2008)
Direct oxidation of H-2 by O-2 to H2O2 and decomposition/hydrogenation of H2O2 have been investigated over Pd/CeO2 catalyst in presence of different halide ions. All reactions were carried out in an aqueous acidic (0.03 M H3PO4) medium at room temperature (25 degrees C) and atmospheric pressure. When different halide ions were added directly to the reaction medium or incorporated in the catalyst, the activity/selectivity of Pd/CeO2 catalyst in the H-2 to H2O2 oxidation changed significantly, depending upon the nature of the halide ions. Different ammonium halides impregnated reduced Pd/CeO2 catalyst calcined under inert (flowing nitrogen) and oxidizing (static/flowing air) gaseous atmospheres revealed that bulk oxidation state of Pd and the nature of the halide ions incorporated into the catalyst cooperatively control the activity/selectivity of catalyst in H-2 to H2O2 oxidation. Both H2O2 decomposition and hydrogenation were found to affect strongly depending upon the nature of the halide ions present in the reaction medium or in the catalyst. Among the different halides, bromide was found the most effective promoter for enhancing the H2O2 yield/selectivity in H-2 to H2O2 oxidation, irrespective of the Pd oxidation state in the catalyst. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Br- ions; H-2 to H2O2 oxidation; H2O2 decomposition; H2O2 hydrogenation; Pd/CeO2 catalyst

Direct synthesis of hydrogen peroxide from hydrogen and oxygen: an overview of recent developments in the process - Samanta, Chanchal (Applied Catalysis A-General, 2008)
Hydrogen peroxide (H(2)O(2)) is an important commodity chemical and its demand is growing significantly in the chemical synthesis due to its ``green'' character. Currently, H(2)O(2) is produced almost exclusively by the anthraquinone auto-oxidation (AO) process. The AO process involves indirect oxidation of hydrogen and thus avoids potentially explosive H(2)/O(2) mixture. However, this large-scale process presents significant safety issues associated with the transport of bulk H(2)O(2). Moreover, the AO process can hardly be considered ail environmentally friendly method. In view of this, more economical and environmentally cleaner routes have been explored for the production of H(2)O(2). The liquid-phase catalytic direct synthesis of H(2)O(2) from H(2) and O(2) offers an attractive green technology for small-scale/onsite production of H(2)O(2). However, the direct synthesis process suffers from two major drawbacks: (i) potential hazards associated with H(2)/O(2) mixtures and (ii) poor selectivity for H(2)O(2) because the catalysts used for H(2)O(2) synthesis are also active for its decomposition and hydrogenation to water as well as for H(2) combustion. These serious issues and the recent developments in the direct H(2)O(2) synthesis are discussed in this review. The roles of protons (H(+)) and halide ions in promoting the H(2)O(2) selectivity are also examined in detail. (C) 2008 Elsevier B.V. All rights reserved
Keywords: Bimetallic catalysts; Direct H(2)O(2) synthesis; Microreactor technology; Pd catalysts

Review on catalytic hydrogenation of biomass-derived furfural to furfuryl alcohol: recent advances and future trends - Racha, Arundhathi; Samanta, Chanchal; Sreekantan, Sreejith; Marimuthu, Banu (Energy & Fuels, 2023)
Biomass is one of the highly abundantrenewable resourcesavailablethat can be converted into several high-value-added products, includingchemicals, biofuels, and advanced materials. To achieve net-zero emissionsand improve biomass application, researchers around the world haverecently focused on expanding biomass processing techniques to value-addedproducts with the eventual goal of industrializing some of the products.In this review, we summarize lignocellulosic biomass derived furfural(FA) and its subsequent hydrogenation to furfuryl alcohol (FAL). Thiswork reviews the various types of hydrogenation catalysts and theirutility in the production of value-added products from FA. There willbe an increase in the demand for selective catalysts and process technologies,as well as an increase in the challenges during valorization, as theusage of biomass to achieve carbon neutrality increases. The reviewaims to provide a concise overview of the advancements in this fieldand the potential for sustainable FAL production. In this paper, wepresent a simple strategy for selecting catalyst systems and associatedprocess parameters that facilitate the highly efficient and selectivevalorization of FA to chemicals or fuel (bioadditives) for industrialuse.

Enhanced Production and Techno-Economic Analysis of Sustainable Biofuel Production via Continuous Hydrogenation of Furfural Using the Cu-ZnO-Al2O3 Catalyst - Saha, Biswajit; Racha, Arundhathi; Chaudhary, Puneet Kumar; Singh, Brijesh Kumar; Samanta, Chanchal; Newalkar, Bharat L. (ACS Sustainable Chemistry & Engineering, 2025)
2-Methylfuran is a perfect green solution on the pathway of finding alternative fuels. We report here for the first time the continuous production of 2-methylfuran (2-MF), a sustainable biofuel from biomass-derived furfural (FFA), over an industrial Cu-ZnO-Al2O3 (CZA) catalyst. The modified coprecipitation method provides a uniformly dispersed crystalline structure to the synthesized catalysts, along with intended copper (Cu) loading achievement. Different Cu loadings affect the catalytic behavior and activity. Hence, CZA catalysts with two Cu loadings of 9.8 and 4.7% were studied in detail, denoted as C1 and C2, respectively. The catalysts were characterized via XRD, N-2 adsorption, H-2-TPR, NH3-TPD, XPS, ICP-MS, and TEM. Remarkably, the prepared catalysts demonstrate balanced acid sites with mesopores, a high surface area and pore volume, and better controlled nanoparticle size promoting catalytic activity. TEM and H-2-TPR studies reveal a better Cu dispersion. Existence of Cu2+ and Cu (+) even after reduction by XPS study proves the efficiency of the synthesized catalysts. Furthermore, TGA indicates the stability of CZA catalysts. To understand catalytic activity and selectivity, the investigation was carried out in a packed-bed fixed-bed stainless steel reactor. Better physiochemical properties result in high FFA conversion of 33.8% and selectivity of 99.6% for 2-MF. No side products were formed during reaction otherwise improbable via the continuous method. Compared with available literature, the CZA catalyst was found to exhibit superior catalytic performance. The reaction kinetics of furfural hydrogenation to 2-methylfuran was investigated, and it was found that the reaction order is high, and the activation energy was 61.2 kJ/mol. The rate constant k clearly obeyed the Arrhenius law from 180 to 220 degrees C. In addition, evaluation of reaction kinetics also indicated the absence of ring hydrogenation and decarbonylation products, which is difficult to achieve. Finally, the process shows significant economic viability, which resulted in the minimum levelized production cost for 2-methylfuran of 173,068.16 \$/ton with 78.32% overall energy efficiency.
Keywords: 2-methylfuran (2-MF); continuous production; Cu-ZnO-Al2O3; economic viability; furfural; green synthesis

Integrated flue gas CO2 capture and conversion to formate: a sustainable approach - Kumar, Rohit; Majumder, Supriyo; Singh, Chadrodai Pratap; Samanta, Chanchal; Newalkar, Bharat L.; Krishnamurty, Sailaja; Das, Raj Kumar (ChemSusChem, 2025)
Industrial CO2 emissions, characterized by dilute streams and impurity complexity, demand energy-efficient mitigation strategies beyond conventional capture technologies. Here, an integrated CO2 capture and conversion (ICCC) system is reported employing a heterogenized iridium catalyst-hydroxyquinoline-ligated Cp*Ir-Cl immobilized on amine-functionalized silica-that directly converts CO2 from synthetic flue gas containing SOx, NOx, and O2 to formate with 100% selectivity. The catalyst delivers remarkable activity, achieving turnover numbers up to 10,286 within 16 h. Density functional theory reveals that its square pyramidal geometry, induced by the hydroxyquinoline ligand, enhances Ir-N(ring) bond strength and electronic delocalization, thereby improving hydration energy, structural robustness, and catalytic efficiency. Importantly, the catalyst system demonstrates excellent durability, maintaining full activity over five regeneration cycles. Hydrogenation in a 1 M DABCO medium, followed by thermal decomposition of the amine-formate adduct at 150 degrees C, enables efficient lean amine regeneration, allowing subsequent flue gas capture and formate production without performance loss. This closed-loop strategy delivers a sustainable, contaminant-tolerant, and recyclable CO2-to-formate platform with strong promise for scalable industrial deployment.
Keywords: CO2 capture; flue gases; integrated capture and conversions; net zero future; Recycle